Community-engaged curriculum development using racial justice and biomedical lenses to address COVID-19 vaccine hesitancy in black individuals with rheumatologic conditions - Osaghae, Eseosa Olive; Sirek, Greta; Roberson, Tonya; Chandler, Mia; Childs, Ariel; Crespo-Bosque, Monica; Curry, Gina; Dhand, Amar; Dollear, Mary; Eggleston, Alice; Ezeh, Nnenna; Fleurissaint, Dieufort; et al. (Frontiers in Public Health, 2025)
Despite the efficacy of the COVID-19 vaccine in reducing mortality and illness severity, racial inequities in vaccination uptake persist. Among individuals with rheumatologic conditions who are often immunocompromised, the impact of disparities in preventive care threatens to widen existing inequities in adverse outcomes related to COVID-19 infection. There exists an urgent need to develop interventions that reduce COVID-19 vaccine hesitancy and promote vaccine uptake. We leveraged long-standing community-academic partnerships in two cities to develop a curriculum that will be part of an intervention to decrease COVID-19 vaccine hesitancy within Black communities. We describe the collaborative efforts that resulted in the creation of two interactive virtual curricula with similar core content but different theoretical lenses. One lens uses a racial justice approach to acknowledge the effects of historical and current structural racism on vaccine hesitancy, the other utilizes a traditional biomedical lens. In a future trial, we will compare the efficacy of these curricula to empower Black individuals identified as Popular Opinion Leaders (POLs), or trusted community members with large social networks, to disseminate health information to promote COVID-19 vaccine uptake. Strategies to reduce racial inequities in COVID-19 vaccine uptake must begin with accurately identifying and empathetically acknowledging the root causes of vaccine hesitancy, as well as addressing nuanced concerns that drive vaccine avoidance among Black individuals. Community engagement and collaboration are central in creating interventions to develop and test culturally relevant strategies, as observed with our curricula, that bridge scientific efforts with community concerns and practices.